Silver and Culinary MSMEs Assistance in the Purbayan Tourism Village through Synergized Promotional Design - Wiyatiningsih Wiyatiningsih; Kristian Oentoro; Winta Tridhatu Satwikasanti; Marcellino Aditya Mahendra (Journal of Innovation and Community Engagement, 2023)
Purbayan Tourism Village is one of 17 tourist villages that received a decree from the Yogyakarta City Government, located in Kotagede. This area has a unique cultural potential that exhibits both historical and cultural wealth  in the form of traditions that exist even today. These traditions include traditional culinary arts, silversmithing and batik craft. However, the potential of this cultural heritage is not visible when compared to the development of the Purbayan Tourism Village. Promotional efforts from business groups and tourism are lacking synergy. Based on these problems, this community service activity aims to assist Micro, Small and Medium Enterprises (MSMEs) to design synergistic tourism promotions. MSMEs that became community service partners are Kopi Lumbung Mataram culinary shop and Studio 76  silver art school. The implementation of this activity uses a user-centered approach to design thinking. In this method, partners as users are actively involved in Focus Group Discussions and workshops on content design and tourism promotion strategies in synergy. The activities described in this paper are understanding, observing, defining point of view, and ideation phase of design thinking. The activity resulted in the promotion concept of Studio 76 silver art school in the form of a draft booth design for silver making exhibitions and photography designs for culinary products of Warung Kopi Lumbung Mataram. Promotion synergy between the two MSMEs is carried out by combining the two tourism service products into an interactive exhibition. The collaboration of these MSME’s aims to promote and increase the number of visitors to the area.